Eid ka din aur mukhtalif kaahaniyan - Shahab, Skiekh (Children Publication Karachi, 2012)
A collection of stories centered around Eid, this book likely contains various tales about celebrations, family, and traditions. It might teach children about the significance of Eid and its customs.